The Current Use Contraception in Indonesia - Nina Indriyawati; Kun Aristiati Susiloretni; Najib Najib (JURNAL KEBIDANAN, 2019)
In this report married couple tend to use modern contraception rather than traditional. The objective of the research was to describe the contraceptives methods of family planning among marriage couple. Methods was used nationally representative data from the Indonesian Demographic Health Survey (IDHS) 2017. This was cross-sectional household survey data, designed to be representative at the national, rural-urban, and provincial level. There were 47,963 households respondents targeted, from 33 provinces and 497 districts/cities. The data were selected from all households with currently married women age 15-49 years.  The descriptive analyze was used in this research. Results showed 53.95% of married women were currently using the modern methods of contraception and 6.64% traditional method while 39.42% were not using any method. Among women they prefer to using pill, implants, injections, and IUD than sterilization 11.62%, 5.02%, 4.18%, 4.17% and 3.74% respectively. Additionally, among men prefer used Male condom (2.33%) rather than Male sterilization (0.14%). In conclusion the unmet need of contraception is reducing and people are moving towards modern contraception instead of permanent methods, which in turn accelerates the improvement in women’s health.